Analysis of Types of Occupational Health and Safety Risk (K3) in Erection Work - Sobirin, Mohamad; Putra, Almie Noegraha; Fertilla, Novika Candra; Susanti, Irriene Indah (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
Infrastructure Development Certification of Human Resources Deputy Building 3 is planned as one of the supporting facilities to improve the quality of human resources, especially in the environment Badan Siber dan Sandi Negara, Indonesia. The purpose of this study is to find out the results of the analysis of the types of risk of K3 in the erection work in Project Pembangunan Infrastruktur Sertifikasi SDM Badan Siber dan Sandi Negara and know the types of K3 risks that play the most role that occur in erection work in Project Pembangunan Infrastruktur Sertifikasi SDM Badan Siber dan Sandi Negara. Using the research method of the survey method that will be validated by K3 Experts. The survey results from the respondent questionnaire were processed using the SPSS (Statistical Package for Social Science). To analyze risk, use the result of multiplying the average opportunity value and the average impact value.